“Taking advantage of emptiness”? - Pier Paolo Viazzo; Roberta Clara Zanini (Revue de Géographie Alpine)
After a century of unbroken demographic decline there are signs in many sectors of the Alpine crescent of a trend reversal which looks especially surprising in those areas (notably the French and Italian Alps) that had been affected by severe depopulation since the second half of the 19th century. In a stimulating analysis of socio-demographic changes in a French Alpine district, Cognard (2006) surmises that depopulation, however disastrous in many ways, nevertheless paved the way to opposite dynamics of repopulation and economic recovery by leaving “empty spaces” which new inhabitants have been able to fill socially and economically, thus taking advantage of the emptiness created by years of emigration. This insight is closely reminiscent of recent anthropological work which suggests that cultural creativity needs space to express itself and that “thick” culture and strong social structures are less favourable to the blooming of creativity than thin and impoverished cultures and weak social structures. This article explores the possibility that the French and Italian Alps, while disadvantaged by their greater demographic fragility, might on the other hand be paradoxically advantaged by the wider spaces for creativity, economic as well as cultural, left by depopulation.